2014
DOI: 10.1016/j.jpsychores.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive adaptation theory as a predictor of adjustment to emerging adulthood for youth with and without type 1 diabetes

Abstract: Objective: The purpose of the study was to determine whether resilience, defined by cognitive adaptation theory, predicted emerging adulthood outcomes among youth with and without type 1 diabetes. Methods: Youth with (n = 118) and without type 1 diabetes (n = 122), who were part of a previous longitudinal study during adolescence, completed on-line questionnaires during their senior year of high school and one and two years later. They were average age 18, 53% female, and 93% white. Questionnaires assessed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Additionally, the results of the present research are in line with previous studies reporting the importance of such protective factors, namely psychosomatic health (Suris, Bélanger, Ambresin, Chabloz, & Michaud, 2011), resilience (Guilera, Pereda, Paños, & Abad, 2015;Helgeson, Reynolds, Siminerio, Becker, & Escobar, 2014;, self-regulation (Gois et al, 2012) and social support (Békési et al, 2011;Wu, Geldhof, Roberts, Parikshak, & Amylon, 2013). Resilience, social support, symptom's control and self-management may allow a good adaptation in adolescents, while facing adverse health conditions and potentially stressful new situations, and help to reduce stress, increase control and improve outcomes in HRQoL.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the results of the present research are in line with previous studies reporting the importance of such protective factors, namely psychosomatic health (Suris, Bélanger, Ambresin, Chabloz, & Michaud, 2011), resilience (Guilera, Pereda, Paños, & Abad, 2015;Helgeson, Reynolds, Siminerio, Becker, & Escobar, 2014;, self-regulation (Gois et al, 2012) and social support (Békési et al, 2011;Wu, Geldhof, Roberts, Parikshak, & Amylon, 2013). Resilience, social support, symptom's control and self-management may allow a good adaptation in adolescents, while facing adverse health conditions and potentially stressful new situations, and help to reduce stress, increase control and improve outcomes in HRQoL.…”
Section: Discussionsupporting
confidence: 92%
“…Resilience, social support, symptom's control and self-management may allow a good adaptation in adolescents, while facing adverse health conditions and potentially stressful new situations, and help to reduce stress, increase control and improve outcomes in HRQoL. Therefore, these variables can be considered promising candidates for future interventions (Chao, Whittemore, Minges, Murphy, & Grey, 2014;Gaspar et al, 2012;Guilera et al, 2015;Helgeson et al, 2014). Moreover, because literature has previously indicated that adolescents with chronic conditions who need to develop more disease-related skills (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…One longitudinal study found that thought suppression during EA predicted ED symptoms in female university students three months later, when controlling for ED symptoms at the earlier time-point (Collins et al, 2014). Another study compared a T1D group and non-T1D group, and found that a self-esteem, mastery and optimism composite appeared to negatively predict EDs symptoms in EAs with T1D but not those without (Helgeson et al, 2014). This study did not include a comparison group of adolescents or adults; it is therefore not possible to determine the extent to which such psychological factors are uniquely relevant to EAs.…”
Section: Etiology Of Eating Disorders During Emerging Adulthood Psychmentioning
confidence: 99%
“…Those with type 1 diabetes scored lower on perceived competence, including global self-worth, than the comparison group at the 10-year follow up. In a more recent study, the self-esteem of young adults with and without type 1 diabetes was examined as part of a resilience or cognitive adaptation index that included self-esteem, mastery, and optimism [57]. Across the three annual assessments, those with type 1 diabetes scored lower on the resilience index than those without type 1 diabetes.…”
Section: Psychosocial Needsmentioning
confidence: 99%
“…Specifically, the group with the deteriorating glycemic control was most likely to be characterized by a low score on positive self-concept [63]. In a longitudinal study of young adults with and without type 1 diabetes, a resilience index, predicted an array of positive young adulthood outcomes, including enhanced psychological health, better relationship functioning, reduced risk behavior, and positive vocational outcomes [57]. In some cases, the links were stronger for those with than without type 1 diabetes.…”
Section: Psychosocial Needsmentioning
confidence: 99%